Patterns of physical activity parenting practices among parent-adolescent dyads who participated in a cross-sectional internet-based study - Jessica L. Thomson; Alicia S. Landry; Tameka I. Walls (BMC, 2021)
Abstract Background While research exploring relationships between individual parenting practices and child physical activity (PA) exists, little is known about simultaneous use of practices. Hence, study objectives were to determine patterns of PA parenting practices and their associations with demographic, anthropometric, and PA measures in a large sample of parents and their adolescent children (12-17 years). Methods Dyadic survey data from Family Life, Activity, Sun, Health, and Eating (FLASHE), a cross-sectional, internet-based study, conducted in 2014 were analyzed using latent class analysis on 5 PA parenting practices - pressuring, guided choice, expectations, facilitation, and modeling. Self-report model covariates included adolescent age and parent and adolescent sex, body mass index category (based on height and weight), legitimacy of parental authority regarding PA (PA-LPA), and moderate-to-vigorous PA (MVPA). Results Based on 1166 parent-adolescent dyads, four latent classes were identified representing a continuum of practice use (high to low) - Complete Influencers (26%), Facilitating-Modeling Influencers (23%), Pressuring-Expecting Influencers (25%), and Indifferent Influencers (27%). Compared to dyads with parent underweight/healthy weight, dyads with parent overweight/obesity had 84% higher odds of belonging to Indifferent Influencers. Compared to dyads with adolescent underweight/healthy weight, dyads with adolescent overweight/obesity had 50 and 46% lower odds of belonging to Facilitating-Modeling and Indifferent Influencers. Odds of belonging to Pressuring-Expecting and Indifferent Influencers were less than 1% lower for every 1 min/day increase in parent MVPA and 2 and 4% lower for every 1 min/day increase in adolescent MVPA. Compared to dyads with high parental and adolescent agreement with PA-LPA, dyads with low agreement had between 3 and 21 times the odds of belonging to Facilitating-Modeling, Pressuring-Expecting, or Indifferent Influencers. Conclusions Findings suggest that parents utilize distinct patterns of PA practices ranging from use of many, use of some, to low use of any practice and these patterns are differentially associated with parent and adolescent PA. When planning PA interventions, a counseling or intervening approach with parents to use combinations of practices, like facilitation and modeling, to positively influence their adolescents' and possibly their own participation in PA may prove more efficacious than parental pressuring or lack of practice use.